(untitled) (ModaPalavra e-periódico, 2021)
The audiovisual project involves countless different professionals in actions that need to be coordinated. For these actions to be more fluid, visual project management can be used. This article aims to improve the scheme proposed by Krupahtz (2018) using visual project management. For this purpose, the areas of production design and visual project management were contextualized to make clear the interaction between them. As a methodological approach, it was used the Lemming method, by Teixeira (2018). As the result, there is the elaboration process of a visual model according to the method and it is described the creation of a visual panel that contemplates the pre-production phase, with a focus on production design. In the final considerations, it is made some suggestions for future works and presented some interesting potentials for research involving both areas.